Pengaruh latihan asertif dalam memperpendek lama perawatan dan menurunkan gejala risiko perilaku kekerasan - Budi Priyanto; Iman Permana (Health Sciences and Pharmacy Journal, 2019)
Violent behavior cause of mental disorder can occur to yourself or others, with more prevalence experienced by men than women. Assertive training can be believed that decrease of violent behavior risk. The study aims to determine the effect of assertiveness in shortening the length of treatment and reducing the risk of violent behavior symptoms in maintenance room at RSUD Banyumas. The method used was Quasi experiment pre-post test with control group with assertive training treatment. The research sample was 34 patients with risk of violent behavior, 17 respondents from the intervention group and 17 respondents from the control group by consecutive sampling. The instrument in this study used a questionnaire data of respondent demography, observation of behavior response, observation of social respond, questionnaire of cognitive respond, and observation of physic respond in the form of likert scale. Differences in risk of violent behavior are analyzed by t test. The results showed that there was no significant difference in the effect of assertive training in shortening the length of treatment (p value 0,05), but there was a decrease in behavioral response by 6,06 in the intervention group while 2,64 in the control group, a decrease in social response by 5,35 in the intervention group while 2,24 in the control group, cognitive response was 5,59 in the intervention group while 2,71 in the control group, and the decrease in physical response in the intervention group was 3,65 while 2,47 in the control group was significantly (p value 0,05) after assertiveness training. There is no effect of assertive training in shortening the length of treatment, but assertive training has proven to be effective in reducing the risk symptoms of violent behavior.